Program Pembelajaran Membaca Kitab Kuning Melalui Metode Sorogan di Pondok Pesantren Darussalam - Muhammad Ansori; Wildan Habibi (LP3M IAIFA Kediri, 2020)
This research was conducted to find out how the Implementation of Learning to Read the Yellow Book Through the Sorogan Method in Pondok Pesantren Darussalam Dnn. Sumbersari Ds. Kencong Kec. Kepung Kab. Kediri. The sorogan method is one of the traditional methods applied in Pondok Pesantren Darussalam to help students in reading and understanding the yellow book which is considered still effective and relevant applied in Pondok Pesantren Darussalam. This research intends to understand the phenomena of what is experienced by research subjects for example: behavior, perception, actions thoroughly, and describing with the form of words and language, in a special context that is natural and by utilizing various methods of ilmiyah. To capture concrete data in research in the field, case studies are used to explain and elaborate comprehensively on the various aspects of an individual, a group, an organization (community), a program, a social situation. The results showed that learning with the application of this sorogan method is effective in educating students to be more active in learning and understanding the yellow book because individual teaching and learning activities can increase the activeness of students in discussing problems and solving them, with the application of this sorogan method will lead to a diverse learning process.